THE DYNAMICS OF SOCIAL SOLIDARITY IN URBAN YOUTH DELINQUENCY: A Case Study of Bengkulu City - Nindi Yulia Puspita Sari; Panji Suminar; Diyas Widiyarti (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2025)
This study analyzes recurring collective delinquency among adolescent gangster groups aged 15–18 years in Bengkulu City, focusing on social dynamics and post-criminal activity adaptation. Employing Émile Durkheim's Mechanical Solidarity Theory, a descriptive qualitative method with in-depth interviews was applied to informants actively involved in 2024. Results indicate that adolescent involvement is driven by strong Mechanical Solidarity formation, where social cohesion, trust, and daily interactions serve as primary bonds, compensating for weak conventional social ties indicated by family emotional neglect and structural gaps in residential environments. This solidarity generates Delinquent Collective Consciousness, manifested through repressive law and driven by collective deindividuation. Crucially, 2025 findings reveal strategic adaptation: the group's decision to cease criminal activities, triggered by increased legal risks (formal social control), while maintaining solidarity through non-criminal activities. This confirms that for adolescents, preserving social bonds outweighs continuing criminal acts. The study concludes that Delinquent Mechanical Solidarity represents a functional response to affection deficits and limited community involvement in Bengkulu.